Efficacy of sugar alcohols and sugars in protein stabilization during freezing, freeze-drying, and air-drying - Sun Wendell Q.; Luo Yongqi (Frigid Zone Medicine)
Cold-acclimated organisms accumulate low molecular weight organic solutes such as sugar alcohols and soluble sugars. This study aimed to compare the efficacy of five sugar alcohols and 14 soluble sugars in stabilizing proteins under freezing, freeze-drying, and air-drying stresses.